Color atlas of vascular diseases - Diehm, Curt; Allenberg, Jens-Rainer; Nimura-Eckert, Keiko; Veith, Frank J. (Springer Berlin Heidelberg Imprint: Springer, 2000)
This book provides angiologists and vascular surgeons with a comprehensive survey covering all aspects of vascular diseases from diagnosis to treatment. All clinical pictures are documented with pathological pictures, angiograms or X-rays. Specific cases of differential diagnosis are included as are surgical photographs concerning the treatment of the diseases. The book describes all vascular diseases from arterial, venous to lymphatic lesions. It combines interests of vascular surgeons, angiologists, radiologists and cardiologists in a unique atlas and text combination of vascular medicine
Keywords: Atlas; Gefäßkrankheit